Analisis Putusan Hakim Peradilan Agama Jember Terkait Cerai Gugat Nomor 5577/Pdt.G/2023/PA.Jr Perspektif Madzahibul Arba’ah - Lukman Hakim (MASADIR: Jurnal Hukum Islam, 2025)
Abstract: Khulu' divorce (cerai gugat) is a form of divorce initiated by the wife based on grounds stipulated in Indonesian legal provisions, including Law No. 1 of 1974 on Marriage, Government Regulation No. 9 of 1975, and the Compilation of Islamic Law (KHI). One of the recognized reasons, as stated in Article 116 letter (f) of the KHI, is the continuous conflict and disputes between husband and wife with no hope of reconciliation. This study aims to analyze the decision of the Religious Court of Jember in Case Number 5577/Pdt.G/2023/PA.Jr regarding a khul? divorce from the perspective of the four Sunni schools of Islamic jurisprudence (madzhab al-arba‘ah). The research employs a normative-juridical approach using descriptive-qualitative analysis of court decisions and classical fiqh arguments. The findings reveal that the judge's legal reasoning in granting the divorce is valid under Indonesian positive law and aligns with Islamic legal principles. The decision was rendered in absentia (verstek) and resulted in the pronouncement of one irrevocable minor divorce (?al?q b??in sughr?). The study concludes that the ruling does not contradict the doctrines of the four madhhabs and upholds the protection of women's rights within the religious court system.